A COMPARATIVE HAPPINESS AND UTILITY ANALYSIS BETWEEN MORTGAGE FINANCED OWNER-OCCUPATION AND RENTING - Osala, Alexandra (My University, 2008)
Yesterday’s struggle to survive has transformed into a struggle towards happiness and utility. As many seem to believe that mortgage financed owner-occupation is the key to happiness it is important to study how a mortgage-financed apartment affects peoples’ overall happiness. The cyclical housing market possesses a risk for a middle income person, also interest rates can rise, jobs are less permanent and may require moving. Having timed the purchase wrong and being forced to sell can be costly. Increasing interests, damages, renovations, on top of other loan costs and amortizing can drive down the disposable income unnecessarily tight also without any major other factors. The theoretical key is that money does not cause happiness, but lack of it typically results in unhappiness and stress, also that a person maximizes utility when each unit gives same satisfaction. The used NPV model suggest middle income person without savings to mortgage finance and rich to rent, but this view does not take stress, life situation changes etc into account. As life and the economy is unpredictable and happiness theory shows stress and risk factors of owning could cause more unhappiness than the potential gain in worth of the apartment ever could increase happiness, middle income people are encouraged to carefully consider the owning option and compare it to renting without prejudice.
Keywords: Happiness; utility; owner-occupation; renting; NPV; fi=Kansantaloustiede|en=Economics|